Pterygium size and effect on intraocular lens power calculation. Issue 11 (November 2016) - Koc, Mustafa; Uzel, Mehmet Murat; Aydemir, Emre; Yavrum, Fuat; Kosekahya, Pinar; Yılmazbaş, Pelin
Abstract : Purpose : To evaluate the effects of pterygium on biometry measurements and the relationship between these effects and pterygium size. Setting : Ulucanlar Eye Hospital, Ankara, Turkey. Design : Prospective comparative study. Methods : Patients who had unilateral primary pterygium excision were included in the study group. Anterior segment photographed images were taken of eyes with pterygia to calculate the pterygium length and area using the ImageJ program. Preoperative and 3‐month postoperative biometry measurements (Lenstar LS900) were obtained for eyes with pterygium and their healthy fellow eyes (control group). Results : Thirty‐two patients with pterygium (mean age 63.31 years ± 7.18 [SD]) were included. The mean pterygium length was 3.07 ± 0.81 mm, and the mean area was 6.26 ± 2.07 mm 2 . The preoperative intraocular lens (IOL) power calculation with all formulas were higher than postoperative and control values ( P < .001). The mean changes were 0.47 diopter (D) for the SRK II, 0.59 D for SRK/T, 0.47 D for Hoffer Q, 0.39 D for Haigis, and 0.38 D for Holladay 2 formulas after pterygium surgery. Positive, significant, and moderate correlations were found between the pterygium size and the change in IOL power. Pterygia longer than 2.40 mm and larger than 5.45 mm 2 created at least equal to or more than 0.5 D deviation in the IOL power calculations. Conclusion : If the pterygium size is larger than 2.40 mm or 5.45 mm 2 and simultaneous surgery is planned, the implanted IOL power should be at least 0.50 D smaller than the calculated power. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.